Colposcopy results in Smear negative, High-risk HPV positive patients - Deha Denizhan Keskin (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2018)
Cervix cancer is an HPV (Human papillomavirus) related cancer, and HPV positivity is necessary even if there is no cytology abnormality. We aimed to determine the ratios of 13 high-risk HPV types in cases with high-risk HPV positivity without cervical smear pathology referred to our clinic and to determine the relation of HPV types with age, parity, menopausal status, and abnormal histopathological results. Two hundred forty-one cases included in the study, which referred to us because of HPV positivity and colposcopically biopsied between January 2014 to January 2018. HPV prevalences were investigated. The relationship between HPV types and variables such as age, parity, menopausal status examined. The mean age of 241 patients included in the study was 46,1+8,8. The parity average was 2,4+1,1. Sixty-five of the patients (27%) were postmenopausal. Of the 241 HPV-positive patients, 172 (71,4%) had only high-risk HPV viruses. The frequency ranking of HPV types was as follow; 16, 31, 51, 56, 18, 52, 35, 58, 39, 68, 45, 33 and 59. According to the HPV types, the average ages were as follow; 18 (43,6 years), 33 (40,1 years) and 51 (41,9 years) were younger than the average age. 35 (48,7 years), 39 (48,5 years), 52 (49,1 years) and 68 (51,3 years) were older than the average age. 16 (44,9 years), 31 (47,9 years), 45 (44,3 years), 56 (47,3 years), 58 (46,9 years) and 59 (46,7 years) was similar the average age. There was no significant difference between the parities according to HPV types (2 to 2,7). According to the HPV types, the menopausal state was as follows; 39 (50%), 56 (50%) and 68 (53,8%) mostly observed in the postmenopausal period; A small proportion of 33 cases (12,5%) was postmenopausal. The rate of severe dysplasia according to colposcopic biopsy related with HPV types was; 58 (40%), 56 (30,8%), 18 (28%), 45 (27,3%), 31 (26,1%), 39 (25%), 59 (16,7%), 35 (14,3%), 51 (13,8%), 33 (12,5%), 16 (11,8%), 52 (8,3%). The prevalence of HPV types, the age at which they saw, the menopausal status and the potential for the formation of severe dysplasia are highly variable. We think that routine screening programme, colposcopy indications and vaccination program should cover all HPV types according to data.